Transformasi Globalisasi 5.0: Pergeseran Strategis Dalam Perilaku Konsumen dan Ekosistem Digital Dalam Persfektif UU ITE 2024 - Nia Puspita Hapsari; Agus Nurudin; Nor Laila; Endang Ruswanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research examines how the transformation towards “Globalization 5.0” triggers strategics changes in consumer behavior, and the digital ecosystem, and how these changes requires adjustments to the regulations of the 2024 version of the ITE Law regarding these changes. The era of Globalization 5.0 marks a new chapter in the relationship between technology, behavior, and global business strategy. This transformation is not only marked by the acceleration of digitalization is not only marked by the emergence of a digital ecosystem integrated with local, data driven, and sustainable values. The research aims yo analyze how the shift towards Globalization 5.0 changes consumer behavior and corporate marketing strategies, and corporate marketing strategies in the context of digitalization, and how the regulations of the 2024 version of the ITE Law change. The research method used was a systematic literature review with a qualitative approach. The results show that global business strategies are now transforming into a global digital ecosystem, where companies must adapt marketing strategies that are responsive to local cultures, but based on technologies such as Artificial Intteligence (AI), and the Internet of Things (IoT). The study emphasizes the importance of integrating digitlaization, local cultural values, and consumer behavior as the foundation of competitive strategy in the era of Globalization 5.0. The revised 2024 ITE Law still contains “rubber” articles, potential regulatory overlap (for example, with the Personal Data Protection Law), and weak adaptation to new technologies are identified as regulatory barriers.